The transmission of crime as work in Turkey: Identification and strategic mutuality - Mercan, Boran Ali (Criminology & criminal justice, 2022)
Bourdieusian criminology has produced useful concepts such as the street-criminal field, capital and habitus. In employing these concepts, this article demonstrates the importance of the criminal role model-image, such as the respected career criminal, as an ego-ideal among lower class youths who identify with these role models, acquiring bodily and mental criminal dispositions using the results of ethnographic research conducted in a run-down district in Ankara, the capital of Turkey. Focusing on a non-Western context with an original theoretical articulation, this article further suggests that the affective relationship between these disadvantaged lower class youths and respected older criminals lubricates the youths’ formation of criminal habitus and likewise constitutes a ‘strategic mutuality’ flowing through certain practices in the street-criminal fields. The original finding lies in revealing a strategic affinity transmitting knowledge of criminal techniques and skills across generations, and further making crime as work a reliable source of income for disadvantaged youths.